Illustrated Oxford Dictionary : Revised and Updated. 187 000 definitions and entries, 4500 illustrations. - Metcalf, Jonathan, ....-; Daintith, John, ....-; Thompson, Della, ....- (Oxford : University Press, 2003)
CONTENT: Foreword. How to Use the Dictionary. How to Use the Dictionary. Structure of Entries. Pronunciation. Labels . Forms. Abbreviations. The Illustrated Dictionary. Reference Section. Political Map of the World. Physical Map of the World. Political Map of US and Canada. Physical Map of North America. Countries of the World. The Night Sky. Measurements. Numbers and Symbols. Time. Miscellaneous Information. The Living World. The Animal Kingdom. Geological Time Periods. Grammar and Style. Acknowledgments
Keywords: Beeldwoordenboeken; Engels -- Woordenboeken; Engels